Retraction note: Study of defensive behavior of a venomous snake as a new approach to understand snakebite (Scientific Reports, (2024), 14, 1, (10230), 10.1038/s41598-024-59416-6) - Alves-Nunes, João Miguel [UNESP] (2025)
Retraction of: Scientific Reportshttps://doi.org/10.1038/s41598-024-59416-6, published online 03 May 2024 The Editors have retracted this Article. After publication, concerns were raised about the animal work reported in this paper. The Animal Ethics Committee of Butantan Institute confirmed that the approval granted to the Authors for their research on snakes (Bothrops jararaca) did not include newborn snakes or the use of the “soft stepping” method. All authors disagree with this retraction.